Pengaruh Kemudahan, Keamanan, Dan Resiko Terhadap Minat Menggunakan Ceria Digital Pada Anggota KSPPS BMT Assyafi’iyah KC Metro - Putri, Erica Yuliana; Suyanto, Suyanto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of convenience, security, and risk on members' interest in using the Ceria Digital application. The research is quantitative with an ordinal scale using a questionnaire. Slovin formula sampling probability sampling. The data analysis technique is multiple linear regression, t test, f test, R2 test. The results of the study conclude that convenience has a positive effect on interest in using Ceria Digital. The high level of convenience causes high levels of interest. Security has a positive effect on interest in using Ceria Digital, applications that are increasingly secure generate levels of interest. Risk has a positive influence on interest in using Ceria Digital, each individual's risk management encourages the importance of the benefits obtained.